Gradient projection-type algorithms for solving ϕ-strongly pseudomonotone equilibrium problems in Banach spaces. (2nd September 2022) - Raeisi, M.; Chalack, M.; Zamani Eskandani, G.
Abstract : In this paper, we introduce the concept of ϕ -strongly pseudomonotone bifunctions in Banach spaces and present two simple subgradient-type methods for solving ϕ -strongly pseudomonotone equilibrium problem. Under mild and standard assumptions, strong convergence theorems of the proposed algorithms are established. To illustrate the usability of our results, a numerical example is given in a non-Hilbertian space.